Growth of Jaguar Cichlid (Cichlasoma managuense) juveniles at different oxygen levels - Acosta Nassar, Marco (1992)
The dependence of growth on the dissolved oxygen level was analyzed un juveniles of the guapote tigre, Cichlasoma managuense, in a recirculated system. The guapote tigre is relatively tolerant to low oxygen levels, averaging only a 17% reduction in growth rate ppm oxygen in the range between 2 and 5 ppm.